SOCIO-PHILOSOPHICAL ANALYSIS OF THE ESOTERIC PICTURE OF THE WORLD - Toyirkulovich, Khidirov Mustafo (The journal of contemporary issues in business and government, 2022)
Socio-cultural changes taking place around the world require the study the trends in the philosophical of the world. Advances in science and technology have made it possible for humanity to discover aspects of the scientific landscape that are unknown to mankind. From time immemorial, esotericism has been viewed as a mysterious, unique form of knowledge that stands alongside scientific, religious, and everyday forms of knowledge. The emergence of esoteric knowledge and teachings on the world stage as a result of the crisis of socio- cultural life, the deformation of society in the spiritual and cultural sphere, the development of esoteric ideas after the crisis of traditional religious teachings can be the basis for scientific research.